Mental health of clinic-attending Syrian refugee women in Jordan: associations between social ecological risks factors and mental health symptoms - Mohamad Adam Brooks; Melissa Meinhart; Luma Samawi; Trena Mukherjee; Ruba Jaber; Hani Alhomsh; Neeraj Kaushal; Raeda Al Qutob; Maysa’ Khadra; Nabila El-Bassel; Anindita Dasgupta (BMC Women's Health, 2022)
Abstract Background The mental health of refugee women is often affected by multiple risk factors in their social ecology. Assessing these risk factors is foundational in determining potential areas for intervention. We used the social ecological model to examine risk factors associated with self-reported mental health symptoms among clinic-attending Syrian refugee women in Jordan. We hypothesize that individual (older age, unmarried, have more children under 18, difficulty reading/writing with ease), interpersonal (intimate partner violence [IPV]), community and societal level risk factors (greater number of postmigration stressors), will be associated with depression, anxiety, and post-traumatic stress disorder (PTSD) symptoms. Methods We surveyed 507 women using a cross-sectional clinic-based systematic sampling approach between April and November 2018. We used multivariable regressions to examine associations between different risk factors in the social ecology on depression, anxiety, and PTSD. Additional multivariable regressions explored associations between specific postmigration stressors and mental health conditions. Results We found rates of depression among our sample to be 62.92%; anxiety 57.46%; and PTSD 66.21%. Our hypothesis was partially supported. At the individual level, age was directly associated with anxiety (aOR 1.04, 95% CI [1.02, 1.06]) and PTSD (aOR 1.03, 95% CI [1.01, 1.06]), while marriage decreased odds for depression (aOR 0.41, 95% CI [0.19, 0.92]) and PTSD (aOR 0.36, 95% CI [0.15, 0.87]). IPV was associated with depression (aOR 2.78, 95% CI [1.72, 4.47]); anxiety (aOR 3.30, 95% CI [2.06, 5.27]); and PTSD (aOR 5.49, 95% CI [3.09, 9.76]). Each additional community and societal risk factor (postmigration stressor) increased the odds for depression (aOR 1.32, 95% CI [1.22, 1.42]), anxiety (aOR 1.28, 95% CI [1.19, 1.39]), and PTSD (aOR 1.46, 95% CI [1.33, 1.60]). Conclusion Understanding social ecological risk factors associated with mental health conditions of Syrian refugee women is vital to addressing their mental health needs. IPV and postmigration stressors are consistently impactful with all mental health conditions. IPV resulted in the largest odds increase for all mental health conditions. Multilevel interventions are needed to address mental health risk factors at multiple levels of the social ecology.